(untitled) - Rol, Ruud van der (New York, 1993)
Photographs, illustrations, and maps accompany historical essays, diary excerpts, and interviews, providing an insight to Anne Frank and the massive upheaval which tore apart her world.
Keywords: Amsterdam ( netherlands ),Frank, anne, 1929-1945; Biography,Pictorial works,Juvenile literature,Pictorial works,Juvenile literature